2017
DOI: 10.1111/acer.13495
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with the Methyl Donor Betaine Prevents Congenital Defects Induced by Prenatal Alcohol Exposure

Abstract: Background Despite decades of public education about dire consequences of prenatal alcohol exposure, drinking alcohol during pregnancy remains prevalent. As high as 40% of live-born infants exposed to alcohol during gestation and diagnosed with Fetal Alcohol Syndrome have congenital heart defects that can be life-threatening. In animal models, the methyl donor betaine, found in foods such as wheat bran, quinoa, beets and spinach, ameliorated neurobehavioral deficits associated with prenatal alcohol exposure (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 57 publications
1
27
0
Order By: Relevance
“…The MD, precisely, comprehends many folate-rich vegetables: asparagus, broccoli, artichokes, cauliflower, the famous little cherry tomatoes of Pachino (Ragusa, Sicily, Italy), and spinach. In particular, for the latter ones, it is important to report a study on an avian embryo model in which it was reported that supplementation with the folate-like methyl donor betaine naturally contained in spinach had even protected against the congenital defects induced by prenatal alcohol exposure, surely modulating epigenetic changes [56].…”
Section: Mediterranean Foods/drinks Contained Molecules Which Act As mentioning
confidence: 99%
“…The MD, precisely, comprehends many folate-rich vegetables: asparagus, broccoli, artichokes, cauliflower, the famous little cherry tomatoes of Pachino (Ragusa, Sicily, Italy), and spinach. In particular, for the latter ones, it is important to report a study on an avian embryo model in which it was reported that supplementation with the folate-like methyl donor betaine naturally contained in spinach had even protected against the congenital defects induced by prenatal alcohol exposure, surely modulating epigenetic changes [56].…”
Section: Mediterranean Foods/drinks Contained Molecules Which Act As mentioning
confidence: 99%
“…[4][5][6] As a common environmental teratogen, alcohol consumption during pregnancy has been reported to cause CHD in foetuses. 7,8 Unfortunately, the underlying mechanism remains unclear. Although the events responsible for cardiac development are not known in detail, increasing evidence supports the involvement of altered histone methylation in the regulation of cardiomyogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Even more recently, Karunamuni et al . showed that low concentration betaine could alleviate cardiac defects associated with prenatal alcohol exposure 53 . But, more experimental evidences are needed for the safety usage of betaine in clinical treatment and assisted reproductive technology (ART) because a recent study indicates that maternal supplement of betaine during pregnancy and lactation gives rise to different impacts on growth of F1 and F2 offspring in rat liver 54 .…”
Section: Discussionmentioning
confidence: 99%